2013
DOI: 10.4103/1305-7456.115409
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of marginal accuracy of grade II titanium and Ni-Cr alloy before and after ceramic firing: An in vitro study

Abstract: Objective:The aims of the study are to assess the marginal accuracy of base metal and titanium alloy casting and to evaluate the effect of repeated ceramic firing on the marginal accuracy of base metal and titanium alloy castings.Materials and Methods:Twenty metal copings were fabricated with each casting material. Specimens were divided into 4 groups of 10 each representing base metal alloys castings without (Group A) and with metal shoulder margin (Group B), titanium castings without (Group C) and with metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
2
8
0
2
Order By: Relevance
“…An ivorine right maxillary incisor was prepared for a full coverage all-ceramic restoration with a heavy chamfer margin. Four points were engraved at a distance of 1 mm below the facial, lingual, mesial, and distal margins[ 12 ] [ Figure 1 ].…”
Section: Methodsmentioning
confidence: 99%
“…An ivorine right maxillary incisor was prepared for a full coverage all-ceramic restoration with a heavy chamfer margin. Four points were engraved at a distance of 1 mm below the facial, lingual, mesial, and distal margins[ 12 ] [ Figure 1 ].…”
Section: Methodsmentioning
confidence: 99%
“…The controversial results could be explained by the effects of different factors on the accuracy and adaptation of computer-or hand-made models. Several studies confirm that different prostheses length, 41 materials, 31,42 finishing line configuration, 26,43 and even framework design, 44 and measurement method 31 could affect the accuracy obtained by different fabrication methods.…”
Section: Discussionmentioning
confidence: 98%
“…In the literature, previous study (42,43) were in agreement in two areas, first of all the distortion occurs during the thermal cycling process and second one the timing of the deformation mostly occurs during the oxidation of the alloy. Patil et al (44) observed that small changes continue during the porcelain application process. The results of the presented study show that the ceramic firing cycles changed the marginal gap of the three and four-unit FPD's manufactured by LW, MM and DMLS's techniques .The gap values were decreased after PFP for LW and MM, slight increase were seen in DMLS's group.…”
Section: Discussionmentioning
confidence: 99%